Is it possible to reduce the cooking time of mortadellas using ultrasound without affecting their oxidative and microbiological quality?. (January 2020) - da Silva, Jéssica Soares; Voss, Mônica; de Menezes, Cristiano Ragagnin; Barin, Juliano Smanioto; Wagner, Roger; Campagnol, Paulo Cezar Bastianello; Cichoski, Alexandre José
Abstract: This study evaluated the reduction of cooking time of mortadellas using ultrasound (US, 25 kHz) and the effects on the oxidative and microbiological quality of the product. Three cooking conditions were studied: control, cooking time traditionally adopted by the meat industry; TUS and TWUS: cooking with and without US application and 50% reduction of the traditional cooking time, respectively. The application of US did not increase the peroxide, conjugated dienes, and TBARS indices and did not accelerate the protein oxidation. In addition, no significant changes were observed in the color of the mortadellas subjected to ultrasonic-assisted cooking. TUS and control presented a similar mesophilic, psychrotrophic and lactic acid bacteria counts during storage. The ultrasonic-assisted cooking provided a faster increase and higher homogeneity in the internal temperature of the mortadellas. Therefore, the US can be considered a promising technology to improve the cooking process of mortadellas. Highlights: Ultrasound (US) was used to reduce the cooking time of mortadellas. US provided a higher homogeneity in the internal temperature of the mortadellas. US did not increase the lipid and protein oxidation. US had a positive effect on gel formation and in the microbiological quality.